Keharmonisan Keluarga Di Saat Pasangan Tak Setara (Analisis Fenomena Assortative Marriage) - Jamalludin Jamalludin (Pancanaka, 2020)
The trend of homogamy marriages in Indonesia has decreased, while hypogamy marriages have increased. Differences in characteristics between couples often damage family harmony. This study aims to determine the effect of assortative marriage patterns on the satisfaction of family harmony. The data used are the 2017 Happiness Measurement Survey (SPTK), and the analytical method used is binary logistic regression. This study separates the regression model between men and women. Logit estimation shows that Old assortative marriage influences the satisfaction of family harmony in men. Education assortative marriage influences women on the satisfaction of family harmony. Men who marry younger and more or lower educated women than themselves have the opportunity to be satisfied with the highest family harmony among other assortative marriage combinations. Women who marry older men and have the same level of education as themselves have the opportunity to feel satisfied with the highest family harmony among other assortative marriage combinations. Women are more likely to select partners based on their education while men are more likely to select partners based on age and physical attractiveness.